De ‘coisa’ a sujeito : o processo de construção da legislação antirracismo no Brasil e a luta política do movimento negro - Catoia, Cinthia de Cassia (2016)
Among the political struggle strategies of the Black Social Movement, which has been characterized by their dynamism and elaboration of each historic moment, thedisputes in the brazilian juridical field can be pointed out, mainly those ones related to the construction of ananti-racism legislation, a set of rules which has a goal of the deconstructingracism, prejudice and social discrimination that cross the brazilian political and social institutions and the subjectivity of the subjects. In this way, according to Discourse Analysis, data analysis method used, and the reflections upon the methodological and theoretical approach of the subaltern studies, particularly the postcolonial studies, I seek to analyze in this reseach the process of construction of this anti-racism legislation/ anti-racial discrimination legislation/anti- discrimination legislation. The specific objectives of the research were, therefore, to analyse: a) which discourses were raised in the normative and juridical field about the racial and ethnic issue making possible the construction of anti-racism legislation from 1950 on; b) which events and debates, ocurred between 1940 and 1988, were outlining the three dimensions of the anti-racism legislation presentin the brazilian legal order, and, finally, c) the importance of Black Movement in this process. The disputes of the normative and juridical field to the construction of the anti- racism legislation and to the deconstruction (still unfinished) of the racial and ethnic relations in Brazil, underlined, on one hand, by an institucional racism and, on the other, by the myth of a racial democracy, represented, at the same time: the problem of brazilian law limits in relation to the racial and ethnic issue, ressignifying, therefore, the own notion of State and brazilian nation; and, a political process in which blacks, being political subjetcs/actors, became subjetcs of rigths, a denied status by brazilian law, during the colonization process and slavery, that marked our history until the 19th century, and still in dispute in the contemporary brazilian society.